Secondary producton in brackishwater culture ponds - Aneykutty Joseph (Department of Aquaculture, College of Fisheries, 1988)
Secondary production of zooplankton and zoobenthos (macrobenthos and meiobenthos) of two brackishwater ponds, A and B, each having 0.042 hectare area and connected to the Cochin backwaters, in the instructional fish farm of College of Fisheries, Panangad, Cochin have been studied for three culture periods. Viz, culture I.C. chenos (120 days, during August to December, 1986), culture II. P.indicus (60 days, during January to March, 1987) and culture III.P. monodon (45 days, during mid May to June, 1987).